Communication Strategy to Develop Local E-Marketplace in Samarinda City - Ainun Nimatu Rohmah; Kadek Dristiana Dwivayani; Kheyene Molekandella Boer (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
COVID-19 has impacted micro, small, and medium enterprises (MSMEs) business in Indonesia. One of the efforts of MSMEs to survive is by migrating to the digital market. The city government of Samarinda grabs the opportunity by releasing a mobile application called Behambinan. This study examines the Behambinan communication strategy to empower MSMEs, considering the apps as an innovation for the digital market in Samarinda. The Diffusion of Innovation Theory helps to parse the communication strategies of this innovation. The method used in this study is qualitative descriptive by conducting in-depth interviews with the Communication and Information Office of Samarinda City and its stakeholders as key actors of the diffusion process. The Behambinan application is currently at the dissemination stage to act effectively as the local digital forum for buying and selling. This study found some challenges during the diffusion process. First, MSME players (adopters) have difficulty understanding the application due to the lack of digital literacy and technical issues such as not having a smartphone and high expense for internet quotas to run the application. Second, the misalignment of interpersonal communication between key actors. Third, weaknesses in promotional strategies. This study found that interpersonal communication through localite channels has a significant role in the diffusion process. An integrated communication strategy among key actors and well-planned execution of localite and cosmopolite channels is essential to engage MSMEs and the public.